Sistem Pendukung Keputusan Pemilihan Saham Terbaik Menggunakan Metode SAW dan ROC Pada Subsektor Perbankan - Hanny Caroline; Endang Lestari Ruskan (STMIK Budi Darma, 2024)
Many investors, especially novice investors, think that from stocks they can get profits and wealth just by following recommendations without knowing what they are investing in and without understanding the risks of losses that can arise in the future. So to avoid losses, novice investors must conduct fundamental analysis before making long-term investment decisions. There are so many types of stocks listed on the Indonesia Stock Exchange (IDX) that investors can choose from and in conducting fundamental analysis there are many criteria (financial ratios) that must be considered as a basis for choosing the best stocks, therefore, the role of information technology is needed to help select the best stocks more quickly and precisely using special methods. Information technology that can help this is a Decision Support System. One method in the decision-making process is Simple Additive Weighting (SAW). The assessment capability in this method is more precise and accurate because it is based on the value of the criteria and the specified weights. The weight value will be determined using the ROC method. This study uses 13 criteria in the process of determining the best stocks, namely EPS, ROE, PER, PBV, DPR, NPM, ROI, ROA, DY, DER, QR, CR, and LDR obtained from the questionnaire results. The alternatives used are stocks from 44 banking subsector companies listed on the Indonesia Stock Exchange (IDX). From the calculations carried out, BBCA stock as A7 with a value of 0.920 is the best stock alternative